2023
DOI: 10.3389/fnana.2023.1198042
|View full text |Cite
|
Sign up to set email alerts
|

Axonal mapping of the motor cranial nerves

Abstract: Basic behaviors, such as swallowing, speech, and emotional expressions are the result of a highly coordinated interplay between multiple muscles of the head. Control mechanisms of such highly tuned movements remain poorly understood. Here, we investigated the neural components responsible for motor control of the facial, masticatory, and tongue muscles in humans using specific molecular markers (ChAT, MBP, NF, TH). Our findings showed that a higher number of motor axonal population is responsible for facial ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…A recent study has demonstrated that ZM muscle innervation is at 10% composed by ANS fibers (vs 3.9% for CS) (Tereshenko et al, 2023). Thus, in our study, implicit ANS response to sounds emotional content could also be reflected in ZM reactivity.…”
Section: Discussionsupporting
confidence: 61%
“…A recent study has demonstrated that ZM muscle innervation is at 10% composed by ANS fibers (vs 3.9% for CS) (Tereshenko et al, 2023). Thus, in our study, implicit ANS response to sounds emotional content could also be reflected in ZM reactivity.…”
Section: Discussionsupporting
confidence: 61%
“…Although the sensory component of the facial nerve (CN VII) innervates the external ear and the tongue [49,50] not the skin on the face, we considered sensory feedback to be an intuitive measure of facial nerve health. Indeed recent research suggests that sensory axons in the face play an important role in maintaining facial muscle tone [51]. In patients with intact cutaneous sensory feedback, eye closure was consistently shown to increase with injected charge at various electrode placements around the eye.…”
Section: Discussionmentioning
confidence: 99%